2017
DOI: 10.1016/j.jtcvs.2017.03.138
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of giant paraesophageal hernia repair with 1-year follow-up

Abstract: Objective Evaluating giant paraesophageal hernia (GPEH) repair requires long-term follow-up. GPEH repair can have associated high recurrence rates, yet this incidence depends on how recurrence is defined. Our objective was to prospectively evaluate patients undergoing GPEH repair with one-year follow-up. Methods Patients undergoing elective GPEH repair between 2011 and 2014 were prospectively enrolled. Postoperatively, patients were evaluated at one-month and one-year. Radiographic recurrence was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…2 Several strategies have been reported to reduce recurrence after hiatoplasty, such as pledgeted interrupted nonabsorbable sutures, 3 mesh crural reinforcement, or wedge gastroplasty. 4 In a pilot animal experimental study, Cakmak et al 5 showed that local injection of BTX causes paralysis in abdominal wall muscles, increases the intra-abdominal volume, and decreases the pressure. Considering that the risk for hiatal hernia recurrence may be affected by the intra-abdominal pressure, 2,6,7 our team proposed a preoperative BTX injection strategy for the giant hiatal hernia management.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several strategies have been reported to reduce recurrence after hiatoplasty, such as pledgeted interrupted nonabsorbable sutures, 3 mesh crural reinforcement, or wedge gastroplasty. 4 In a pilot animal experimental study, Cakmak et al 5 showed that local injection of BTX causes paralysis in abdominal wall muscles, increases the intra-abdominal volume, and decreases the pressure. Considering that the risk for hiatal hernia recurrence may be affected by the intra-abdominal pressure, 2,6,7 our team proposed a preoperative BTX injection strategy for the giant hiatal hernia management.…”
Section: Introductionmentioning
confidence: 99%
“…While this group had fewer problems in bladder and bowel functions, the association with GPEH is uncertain. The preoperative quality of life was not measured here, but overall HRQoL improves with a laparoscopic GPEH repair [22].…”
Section: Discussionmentioning
confidence: 99%
“…A recurrent hernia was defined as a hernia with > 2 cm of the stomach above the diaphragm. The hernia was considered small, or minor recurrence, if it was 2 to 5 cm and a large recurrent hernia, or major recurrence, was > 5 cm, as defined in prior studies [18,22,27].…”
Section: Radiological Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…An example of this is Giant Paraesophageal Hernias (GPEH) that are relatively rare and often misunderstood. Stringham et al (6) studied 106 GPEH patients at a single institution and found that surgical repair is safe and carries a low postoperative complication rate. Additionally, the study compared a new, radiographic recurrence definition (any amount of stomach above the diaphragm on barium swallow) to the conventional recurrence definition most often used in GPEH literature (>2 cm or >10% of the stomach above the diaphragm) and found a 1-year radiographic recurrence rate of 32.7% compared to a conventional recurrence rate of 18.8%.…”
mentioning
confidence: 99%